Narratives of Crisis in the Final Reign of Uthman bin ‘Affan: An Evaluation - Ab Halim, Asyiqin (Journal of Al-Tamaddun, 2025)
The reign of Uthman bin ‘Affan can broadly be divided into two distinct phases. The first phase was marked by peace, harmony, prosperity, and significant progress among the Muslim community. In contract, the second phase witnessed increasing turmoil, unrest, disputes, and dissension, culminating in serious discord among Muslims. Historians and scholars have offered varying interpretations regarding the issues that emerged during this period, their underlying causes, and Uthman’s responses to them. This study aims to examine the major problems that arose during Uthman’s reign, including the accusations directed against him, the contributing factors behind these challenges, and the measures he employed to addressed them, particularly his approach to the rebellion and those he faced. This qualitative research based primarily on primary and secondary sources for data collection and analysis. The findings indicate that the accusations against Uthman were largely unfounded, as he possessed legitimate justifications for his actions. Nonetheless, a combination of internal and external factors escalated tension beyond control, ultimately leading to the assassination of the Caliph.